Pérdida de peso y parámetros de calida en huevo fresco de gallina recubiertos a base de polímeros comestibles - Peralta, Milagros (2024)
The application of edible coatings on fresh chicken eggs presents various advantages, such as increasing its useful life, preserving its internal quality, decrease in weight loss, reduction of breaks and vehicleization of compounds antimicrobials to eliminate pathogenic bacteria such as Salmonella spp. The objective of This work was to evaluate the effect of including xanthan gum in a coating sodium alginate base on quality parameters and weight loss during the storage. To prepare the coatings, 3 solutions were used: S1: Sodium alginate (1.5% w/w); S2: Sodium alginate (1.5%w/w), Xanthan gum (0.3%w/w) and Sunflower oil (0.4% w/w); prepared in distilled water with Glycerol (2% w/w) as plasticizer, degassed by sonication; and S3: Cl2Ca solution (2% w/w). HE They used 18 eggs laid per day, purchased from a local supplier. The eggs They were dry cleaned, weighed and randomly distributed in 3 balanced lots, applying two treatments (T): one batch was immersed in S1 (T1), another batch in S2 (T2) and both were immersed in S3 (immersion time in each solution: 1 minute). He The third batch, used as a control (ST), was not subjected to any treatment. The treatments and the control were stored at 8+2ºC for 4 weeks. Weekly The percentage of weight loss was evaluated (Δp%=(initial weight–final weight)*100/initial weight) of the eggs from each batch. In the fourth week they were measured instrumentally (Digital Egg Tester DET600) quality parameters: albumen height (AA), units Haugh (UH), shell breaking resistance (RR) and yolk pigmentation (PY by DSM-YolkFan™). The Δp% was analyzed with repeated measures ANOVA, considering time as factors (t with 4 levels: 1, 2, 3 and 4 weeks), the treatment (T with 3 levels: T1, T2 and ST) and their interaction. Each of the parameters quality was analyzed with an ANOVA of one factor T. Differences were found significant in the Txt interaction (p=0.0033). The means of Δp% for T2 were less than for T1 until the second week (T1= 0.5283±0.1486 % and T2= 0.2583±0.1341 %) and lower than for ST until the third week (Tc=0.8300±0.2235% and T2= 0.4533±0.1965%) (Tuckey's test, α=0.05). The stockings general quality parameters +/- standard deviation were: AA =7.49+2.41 mm, UH = 83.16+14.53, RR = 4.17+1.06 KgF and PY = 6.12+0.86. Statistically, no significant differences were found between the treatments for all quality parameters (α= 0.05) and these values ​​were found within the marketing ranges. The results indicate that the coating that includes xanthan gum reduces the weight loss of the eggs until the third week of storage compared to the control. The applied coatings did not modify the internal quality of the eggs after 4 weeks of storage, so they could be used to incorporate antimicrobial compounds, improving food safety without modifying their quality.